Outcomes of primary stapedotomy using ionomeric cement at incus-prosthesis attachment versus nonuse of ionomeric cement: a prospective case–control study - Ahmed Galal; Mashrab Saggaf; Yasser Shewel; Hani F. Elgarem; Amir Mina (The Egyptian Journal of Otolaryngology)
Abstract Background Stapedotomy is the main stay management of otosclerosis till the present day. Other alternatives are hearing aids and medical treatment. Many complications arise at the step of crimping of the prosthesis. Bone cement is a material that has strong adhesive and osteointegration properties. The aim of the present study is to compare hearing results between bone cement-applied and non-bone cement-applied primary stapedotomy patients at the incus prosthesis attachment. Methods Thirty patients diagnosed with otosclerosis were randomly selected. Classical primary stapedotomy was performed for both groups, except for using GIC over the incus–prosthesis attachment in group A patients. The duration of follow-up was 2 months. Mean thresholds were measured at 0, 1, 2, and 4 kHz frequency levels and used to calculate the primary outcome measurements, which were ABG closure and hearing gain. Results The overall 30 patients’ mean age was 37.2 years. Bilateral disease occurred in 73.3%. Both groups showed significant ABG closure in relation to the preoperative values (P < 0.001). However, ABG closure in cement-used patients was significantly better (P 0.007). The mean for air conduction hearing gain was higher in group A (31.9 dB) than in group B (27.3 dB). However, this was statistically insignificant (P 0.313). Conclusions GIC can improve hearing outcomes in classical primary stapedotomy and potentially reduce postoperative complications and should be considered in routine practice.